Comparative performance evaluation of modified solar cookers for subtropical climate conditions. (June 2023) - Koshti, Bhupendra; Dev, Rahul; Bharti, Ajaya; Narayan, Audhesh
Abstract: Solar cooking has been an attractive way of cooking food using solar energy (which is a form of renewable energy). Two modified solar cookers namely 'Modified solar cooker with an inclined cover (MSCIC)', and 'Modified solar cooker (MSC)' have been designed and tested for the climatic condition of Prayagraj, Uttar Pradesh, India. The present work evaluates the thermal performance of two transparent solar cookers with the same aperture area but with different geometries. The experiments have been conducted with same quantities of water taken in the pots of both the cookers. The effect of various thermal parameters such as 'pot water temperature', 'figure of merits', 'thermal efficiency', 'energy and exergy' with a comparative analysis of modified solar cookers have been analysed. Results show that the First figure of merit for both transparent cookers have been found nearly identical ( F 1 MSCIC = 0.11 and F 1 MSC = 0.106) and Second figure of merit have been found F 2_MSCIC = 0.77 and F 2_MSC = 0.72. Similarly, instantaneous exergy and energy efficiencies have been found 6.1% and 7.8% respectively for MSCIC, and 4.6% and 7.2% respectively for MSC. This indicates that thermal performances of both cookers were comparable. A fair acceptable agreement was found between MSCIC and MSC experimental results also.